Increased efficiency gyroid structures by tailored material distribution. (1st January 2021) - Downing, David; Jones, Alistair; Brandt, Milan; Leary, Martin
Abstract: The gyroid has been identified as a cellular topology suitable for engineering applications and, particularly in its solid-network form, for biomedical applications. Its solid-surface form has received less attention but offers additional benefits of a continuous surface that partitions space and provides large surface area for heat transfer or cell attachment. Through numerical methods it is shown for the first time that under uniaxial loading the solid-surface gyroid distributes loads predominantly within helical substructures. Furthermore, by adjusting the thickness of the load carrying helical regions, the mechanical response can be tuned in different directions. This novel discovery enables more efficient use of material distribution while taking advantage of the unique properties of the solid-surface gyroid. Graphical abstract: Unlabelled Image Highlights: Identification of highly stressed helical subregions within the solid-surface gyroid structure under compressive load. Quantification of the correlation between stress intensity with the dot product of the load direction and local surface normal orientation for the helical subregions. Local thickness adjustment of the helical subregions, enables tuning of the mechanical response in multiple directions. Application of variable local thickness distribution effected an increase in compressive stiffness and strength of approximately 20% at fixed relative density.